2018
DOI: 10.1088/1361-6528/aae4d3
|View full text |Cite
|
Sign up to set email alerts
|

Hole and electron trapping in HfO2/Al2O3 nanolaminated stacks for emerging non-volatile flash memories

Abstract: HfO 2 /Al 2 O 3 nanolaminated stacks prepared by atomic layer deposition have been investigated in terms of their charge storage characteristics for possible application in charge trapping memories. It is shown that the memory window, electron and hole trapping and leakage currents depend strongly on Al 2 O 3 thickness and post-deposition oxygen annealing. Depending on the Al 2 O 3 thickness, postdeposition annealing in O 2 creates different electrically active defects (oxide charge and traps) in the stacks. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…A simulation with the Band diagram tool [14] reveals that an oxide charge of about −6×10 12 cm -2 with a centroid situated in the middle of the BO layer, combined with the dipole potential, could explain the observed Vfb. Note that a negative Qox (−6.4×10 12 cm -2 ) was detected earlier [5] for HfO2/Al2O3 nanolaminates with thicker (~3 nm) Al2O3 sublayers. Hence, it could be suggested that the Al2O3 sublayers contribute a negative charge that is thickness-dependent; for certain thicknesses it might prevail over the positive charge associated with HfO2 and SiO2, thus determining the net negative Qox.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…A simulation with the Band diagram tool [14] reveals that an oxide charge of about −6×10 12 cm -2 with a centroid situated in the middle of the BO layer, combined with the dipole potential, could explain the observed Vfb. Note that a negative Qox (−6.4×10 12 cm -2 ) was detected earlier [5] for HfO2/Al2O3 nanolaminates with thicker (~3 nm) Al2O3 sublayers. Hence, it could be suggested that the Al2O3 sublayers contribute a negative charge that is thickness-dependent; for certain thicknesses it might prevail over the positive charge associated with HfO2 and SiO2, thus determining the net negative Qox.…”
Section: Resultsmentioning
confidence: 53%
“…Since the modern MOSFET technology for ultra-high-density circuits requires the employment of high-k dielectrics in the gate stacks, it is quite tempting to use these materials as charge storage media; moreover, the high-k insulators turned out to be trap-rich materials. Among the various high-k dielectrics, HfO2-based dielectric stacks have been recently pointed out as very promising candidates for replacing Si3N4 in the future CTM generations [1,[3][4][5][6]. The attractiveness of employing HfO2 as a charge-trapping material is additionally reinforced by the fact that the HfO2 MOSFET technology has already reached a state of maturity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the floating gate layer is also anticipated to be a promising constituent in the three-terminal NVM device’s structure for higher charge storage capacity and suitable endurance/retention memory operations [ 8 , 9 , 19 , 20 , 26 ]. Additionally, the charge-trap layer such as HfO 2 , SiN, and redox state molecule has been introduced in the NVM device’s structure to store and erase the charge according to the memory state controlled by a swing in the threshold voltage (V th ) [ 27 , 28 , 29 , 30 , 31 ]. On the contrary, NVM devices based on metallic nanoparticles as a floating gate have gained more advantages, such as higher tapping probability of charges, ensuring the stable probability of retention property in case of defects in the tunneling or control oxide layer, and larger memory window [ 8 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the discrete nature of the NC-based floating-gate, charge leakage due to defects in the underlying thin tunnel-oxide is limited only to a small number of NCs, thus improving the charge retention and endurance characteristics. Moreover, the discreteness of the charge-storage nodes enables multibit-per-cell storage, without resorting to the multilevel approach. , In the recent past, many research efforts have therefore focused on the use of NCs of semiconductors, metals, ,− metal silicides, or high-k dielectrics to form the discrete floating-gate of NVMs. As one of the candidates for discrete charge-storage nodes, metal NCs provide several advantages over their semiconductor counterparts .…”
Section: Introductionmentioning
confidence: 99%